2015
DOI: 10.1002/cjce.22211
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Trimethylamine Removal Process Under Synergistic Effect of Photocatalytic Oxidation and Surface Discharge Plasma Reactor

Abstract: Removal of trimethylamine (TMA) from the air is experimentally investigated by combining photocatalysis with a DBD plasma reactor, at ambient temperature and atmospheric pressure. Many parameters are investigated in this work, such as flowrate, inlet concentration, relative humidity of effluent, and specific energy of discharge. By combining non‐thermal plasma and photocatalysis, a synergy effect on the removal efficiency of TMA has been observed under different experimental conditions. Moreover, we note that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Nanostructured TiO 2 has also been used in many applications such as sensors [12], photocatalysis [13][14][15][16], and solar energy conversion [17]. TiO 2 nanotubes have attracted particular attention because of their high specific surface area [18], high photoactivity [19], and the rapid transfer rate of holes and electron-hole pairs (e − /h + ) photogenerated along the nanotubes [20][21][22]. However, two major factors limit the performance of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructured TiO 2 has also been used in many applications such as sensors [12], photocatalysis [13][14][15][16], and solar energy conversion [17]. TiO 2 nanotubes have attracted particular attention because of their high specific surface area [18], high photoactivity [19], and the rapid transfer rate of holes and electron-hole pairs (e − /h + ) photogenerated along the nanotubes [20][21][22]. However, two major factors limit the performance of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the photogenerated (e − /h + ) pairs exhibit a high rate of recombination due to a high density of crystal defects [23]. To overcome these problems, many strategies have been established, such as doping TiO 2 (metallic or non-metallic dopants) [13,17] and coupling with other semiconductors [19,20,24], which could expand absorption under visible light and improve the lifetime of the photogenerated (e − /h + ) pairs. Recently, it has been shown that the decoration of TiO 2 nanotubes with noble metal nanoparticles can increase their absorption in the visible range, thanks to the surface plasmon resonance (SPR) [25] induced in the metallic nanoparticles in the presence of a light wave.…”
Section: Introductionmentioning
confidence: 99%
“…Like Figures and , Figures , , and adopted the 5×2 geometry for the GA. The rich colours in all three GAs make them very attractive.…”
Section: Examplesmentioning
confidence: 99%
“…A synergy effect on the removal efficiency of the pollutant was observed at pilot scale. Title: “Acceleration of Trimethylamine Removal Process under Synergistic Effect of Photocatalytic Oxidation and Surface Discharge Plasma Reactor.”…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation